Feeding Difficulties and Gastrointestinal Tract Morphology and Innervation in 'Charge' Syndrome. (1st June 2016) - Hudson, A; Macdonald, M; Cloney, K; Steele, S; Berman, J; Blake, K; Stoyek, M; Croll, R; Smith, F
Abstract: BACKGROUND: CHARGE syndrome has been linked to mutations in the CHD7 gene and results in a number of physiological and structural abnormalities. The estimated incidence in the Atlantic Provinces is 1 in 8500 births. Challenges include eating problems, which have a profound impact throughout a child's life and can lead to complications and even death. OBJECTIVES: To investigate feeding difficulties and model the morphology and innervation of the gastrointestinal tract in CHARGE syndrome. DESIGN/METHODS: Three research studies (two clinical, one basic science) were conducted to assess feeding difficulties in CHARGE syndrome. The first study conducted a qualitative analysis of parent interviews to understand packing and problematic feeding behaviors. The second study investigated general eating and GI motility problems by having parents complete a series of feeding questionnaires. The third study modeled CHARGE syndrome in zebrafish by using a morpholino to knock down the expression of CHD7. RESULTS: Study 1: Twenty parents completed a phone interview, describing their child/adult's (2-32 years) adverse feeding behaviors. Parents reported food packing most commonly with bread and pasta (33%), and reported that food was held in cheeks for hours after a meal had ended (35%). Packing was reported to prolong mealtimes for over an hour (30%). Parents were worried about choking during eating (30%).Study 2: Sixty-nine parents of children (age 1-18 years) completed the questionnaires. Those who were tube fed had significantly more gastrointestinal symptoms (stomach pain, nausea, etc.) and worse feeding difficulties than those who were orally fed. The CHARGE characteristics of choanal atre-sia/stenosis and cranial nerve IX/X dysfunction were associated with significantly more gastrointestinal symptoms. Parents identified constipation as a major challenge. Study 3: Immunohistochemistry demonstrated changes in the enteric innervation of the gastrointestinal tract in the CHARGE syndrome zebrafish models. There was decreased branching of the gastrointestinal nerve network surrounding the stomach. Use of fluorescent microbeads demonstrated reduced motility and delayed passage of the microbeads through the gastrointestinal tract. CONCLUSION: These three studies provided a comprehensive analysis of feeding and gastrointestinal difficulties, from mouth to anus, in CHARGE syndrome. They provide a deeper understanding of adverse feeding behaviors, feeding difficulties, and the abnormal morphology of the gastrointestinal system. The information from this study can be useful for general pediatricians and feeding therapy teams who are involved in the care of these individuals starting in infancy. The team-based approach of conducting multiple research projects investigating a common issue may be useful in other genetic disorders.